Barcelona Experience in Resilience: An Integrated Governance Model for Operationalizing Urban Resilience. - Chelleri, Lorenzo (Springer, 2018)
Urban resilience research has been investigating during the last two decades how to reduce or mitigate disaster risks or climate change related threats. A variety of projects, best practices and networks have emerged from these recent experiences, but the gaps between urban resilience theories, research and practices have been increasing when “city resilience” started to be a policy label fitting any urban challenge. This chapter presents a case study, exploring how the City of Barcelona has framed an integrated governance model for managing different initiatives related to resilience. This is but an institutionalist perspective, along which the chapter discusses Barcelona’s past and current capacities for building resilience. Furthermore, it is discussed how the municipality has framed, through leveraging on a dense international network of collaboration and these local experience in resilience, a new city resilience unit that leads in integrated way a range of projects enhancing urban resilience. Promoted as the Barcelona Resilience Model, this chapter offers some critical reflections on how and why this model has been built, launched and supported from industry partners, stakeholders and multilateral agencies.
Keywords: Nachhaltige Stadtentwicklung; Urban Governance; Resilienz; Ökologischer Stadtumbau; Handlungskonzept; Implementierung; Fallstudie